MORPHOMETRICS OF GENUS CASSIA L.FROM KOLHAPUR DISTRICT - S. A. DESHMUKH, (The Bioscan, 2011)
Morphometric study of ten different species of Cassia L. from Kolhapur District was performed with respect to the fourteen different quantitative characters; which includes leaf length, leaflet length, leaflet width, leaflet length/ leaflet width, petiole length, pedicel length, petal length, petal width, fruit length, fruit width, fruit length/ fruit width, seed length, seed width and seed length/ seed width. The dimensions of quantitative characters were measured and subjected to the principal component analysis (PCA) and cluster analysis. PCA results reveals the correlation between all quantitative characters mentioning that four characters which are related with the leaf i.e. leaf length, leaflet length, leaflet width and leaflet length/leaflet width are significant in delimitation of the Cassia L. species. Cluster analysis and dendrogram on the basis of farthest neighbor, mean character difference and constrained clustering strategy shows that the dissimilarities in between Cassia abscus L. and Cassia alata L. is greater while that in between Cassia sophera L. and Cassia occidentalis L. is minimum. Coefficients of Difference values of all the species reveal that Cassia abscus L. and Cassia siamea Lamk. are distinctly separate from each other as they with more significant CD and Cassia occidentalis L. and Cassia sophera L. are closely related with each other, as well as quantitative characters like seed length/ seed width, fruit length/ fruit width, fruit width and petal width has vital contribution in differentiation of the taxa.